Exploring nursing students’ learning experiences within tripartite meetings in nursing home clinical placements: a qualitative study using video-stimulated recall interviews - Ingrid Espegren Dalsmo; Kristin Alstveit Laugaland; Stephen Billett; Else Mari Ruberg Ekra (BMC Nursing)
Abstract Background Nursing students’ clinical learning is premised on experiences in clinical placements in nurse education, with the processes and outcomes of tripartite meetings among the student, nurse preceptor and teacher being central components. The tripartite meetings form the basis and framework for stakeholders’ dialogue and collaboration and have the central purpose of facilitating student learning and development and assessing the students’ achievement against predetermined learning outcomes for the placement period. Students’ experiences with tripartite meetings seems to be an underexplored field, and therefor this study aimed to explore first-year nursing students’ learning experiences within tripartite clinical placement meetings in nursing homes. Design and methods A qualitative explorative and participatory approach was adopted in this study, using the video-stimulated interview method “stimulated recall— dialog and reflection”. This method is based on video recordings with subsequent interviews, where video excerpts were used to support reflection and dialogue. Twenty-one video-stimulated recall interviews were conducted with first-year nursing students (n = 7) to explore their learning experiences within the tripartite meetings. Findings Data was analysed using reflexive thematic analysis as described by Braun and Clarke. Four themes were identified: (1) the importance of structure and preparedness; (2) supportive relations and dialogue essential for learning; (3) a possibility to create a common learning focus; and (4) assessment needs to be comprehensive and performance focused. Conclusions This study highlights that tripartite meetings can be an excellent forum to support the nursing students’ learning process in their clinical placements. Still, consistent and systematic approaches to clinical placement supervision and assessment need to be developed continuously. Therefore, the study’s findings suggest that targeted efforts are warranted to optimise and enhance the learning potential offered in tripartite meetings in clinical education, such as paying a greater attention to the start-up conversation and facilitating comprehensive supervisory and assessment content in the meetings.